PRO KONTRA HUKUM YANG HIDUP DIMASYARAKAT DALAM UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Saragih, Kevin Ryadi; Swardhana, Gde Made (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 5 (2023), 2023)
The existence of living law in the criminal code of the Republic of Indonesia (Undang-Undang Nomor 1 Tahun 2023) has caused debates among the public and academics. The purpose of this legal research paper is to describe two opposing arguments on this matter. The paper uses normatif research methods with a statutory and conceptual approach. The results of the study show contrasting opinions on the existence of living law in the criminal code. Proponents argue that legal pluralism in Indonesia should be utilized to strengthen customary & state law and to help law enforcement solve legal problems in society fairly. However, opponents believe that the application of living law disturbs the principle of legality and has the potential to harm human rights.